2020
DOI: 10.35860/iarej.697009
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of effect of the ceramic coatings with bond-layer coated on piston and valve surface on engine performance of a diesel engine

Abstract: The piston and valve surfaces of diesel engine have been coated with Cr2O3, Cr2O3+50%Al2O3 and Cr2O3 + 75% Al2O3 ceramic powders with bond coat (NiCr) by atmosferic plasma spray (APS) method. The engine performance of the coated engine were compared with the standard engine values by using that the engines tests were applyed repeat for each specimen in an electrical dynamometer in full power 1400 rpm, 1700 rpm, 2000 rpm, 2300 rpm, 2600 rpm, 2900 rpm and 3200 rpm engine speeds. In the results; it has been seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…In the last quarter century, the limited fossil-based resources, have encouraged researchers to explore different alternative fuels [1][2][3][4][5][6]. In addition, increasing environmental concerns as a result of the use of petroleumbased fuels are the other and main reason for these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the last quarter century, the limited fossil-based resources, have encouraged researchers to explore different alternative fuels [1][2][3][4][5][6]. In addition, increasing environmental concerns as a result of the use of petroleumbased fuels are the other and main reason for these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, boronizing will be an economical alternative method to thermal barrier coating (TBC), which requires a very complex assembly and high-cost initial investment. It has been reported that this thermal barrier coating formed on the surface of the machine elements reduces wear and significantly improves the performance of the machine element and its mechanism [22,23]. In many studies in the literature, the effect of boronizing on hardness and wear in AISI 4140 and AISI H13 steels has been examined.…”
Section: Introductionmentioning
confidence: 99%